In what ways students’ socio-economic status affecting academic performance? - Muhammad Abduh; Edi Purwanta; Hermanto Hermanto (Institute of Advanced Engineering and Science, 2023)
Due to the rapid development and dynamics of education, parents are becoming increasingly focused and concerned about their children’s education. Parents have a significant influence on students’ academic performance (AP) based on various perspectives, one of which is socio-economic status (SES). A systematic literature review is required to provide an overview for educators and policy makers in Indonesia to address problems that arise in students’ AP due to SES factors. However, there are limited research studies that systematically review the literature on SES in regards to students’ AP. This study was guided by the preferred reporting items for systematic reviews and meta-analysis (PRISMA) review protocol employing two databases: Scopus and Google Scholar, regarding students’ SES and student AP. There were 316 articles were screened and 51 articles that met the predetermined criteria were obtained. This study performed content analysis to codify, organize categories, and develop themes. Based on the thematic analysis, this study grouped three main themes: SES based on student roles, SES based on teacher roles, and SES based on family roles. This review contributes to the existing literature by providing direction for further research and as a catalyst for developing new literacy related to SES in education.